Respuesta :

kkfoug

Answer:

g(-3) = 23

Step-by-step explanation:

This question is telling us that x = -3. Knowing this, we can plug x into the equation and solve to find g(-3).

[tex]g(-3) = 3(-3)^{2} -4[/tex]

[tex]g(-3) =3(9)-4[/tex]                      Square -3 to get 9

[tex]g(-3) = 27-4[/tex]                         Multiply 9 by 3 to get 27

[tex]g(-3) = 23[/tex]                               Subtract 4 from 27 to get 23

Thus, g(-3) is equal to 23.

I hope this helps! Good luck!

ACCESS MORE